Do teenagers' and parents' alcohol-related views meet? – Analysing focus group data from Finland and Norway. (2nd January 2019) - Simonen, Jenni; Törrönen, Jukka; Tigerstedt, Christoffer; Scheffels, Janne; Moan, Inger Synnøve; Karlsson, Nina
Abstract: Aims : This study analyses how Finnish and Norwegian teenagers and parents of teenagers perceive the appropriateness, desirability or harmfulness of different drinking situations. The focus is on whether teenagers and parents perceive the situations similarly or differently. Methods : Our data consist of focus group interviews from Finland and Norway with teenagers aged 14–17 years ( n = 8 groups, n = 44 participants) and parents ( n = 8 groups, n = 38). Three pictures portraying different drinking situations were presented to the participants, who were asked to describe (1) what kind of situation the picture depicts, (2) whether the way of drinking in the picture was acceptable or not and (3) whether they identified with the situation or not. Findings : Our analysis showed that teenagers and parents defined the situations similarly and applied rather similar criteria when assessing the appropriateness of drinking. The most important criteria related to the amount and the way of drinking, and whether or not children were present in the situation. Regarding the identification with the situations, teenagers seemed to have somewhat stricter attitudes towards intoxication than adults, which can be perceived as a sign of an ongoing trend of decreasing youth drinking. Conclusions : Overall, our analysis suggests that the alcohol worlds of parents and teenagers resembled each other, supporting the notion that the generational gap between parents and teenagers is diminishing.